LEGAL PROBLEMS OF THE FORMATION OF A SINGLE ENVIRONMENTALLY SAFE SPACE OF THE EAEU MEMBER STATES - A. Zakharin; R. Nutrikhin (Гуманитарные и юридические исследования)
The article is devoted to the analysis of problems and the identiication of effective mechanisms for ensuring environmental safety in the conditions of the functioning of the common economic space of the EAEU member states. The need for the stable development of land and other natural resource, environmental protection relations, environmental law and order, the introduction of mechanisms for the harmonization or unification of the norms of law in the context of the desire of the member states of the Eurasian Economic Union to strengthen national economies and achieve the growth of their competitiveness on a global scale economic system. The progressive development of the Eurasian Economic Union and the need for the implementation of signiicant infrastructure and investment projects to implement the concept of sustainable development in the EAEU member states leads to the strengthening of integration processes aimed at ensuring environmental safety and eficient use of natural resources in this international organization. The legal mechanism for the implementation of such interaction for the EAEU states can be considered harmonization, which allows for the coordination of common approaches and concepts, joint development of legal principles and the development of joint solutions on problems that are urgent for all states. Legal problems of the development of the integration of legal regulation of environmental safety in the EAEU countries are determined by the lack of uniform approaches and existing regulatory legal acts on environmental safety, various forms, plurality, declarativeness and inconsistency of national legislation regulating environmental safety. The development and consolidation in the EAEU acts of the legal foundations of environmental safety will not only bring the legislation of the Union member states in this area to a new qualitative legal level, but also create the basis for effective cooperation between states, serve as an effective effective cooperation between states, and serve as an effective means of fulilling international obligations in the ield of environmental protection and rational use.